Clinical variation in Lowe syndrome: what and how? - Brewer, Eileen D. (Frontiers in Cell and Developmental Biology, 2025)
Lowe syndrome is an X-linked disorder caused by mutations of the OCRL gene which encodes the enzyme inositol polyphosphate-5-phosphatase OCRL (Ocrl1) and is expressed in almost all body cells. Clinical characteristics involve kidney, brain, eye, muscle, bone, teeth, testes, skin and thrombocytes. Clinical phenotypes are heterogenous among families and even among affected boys in the same family. All have kidney disease varying from severe manifestations of Fanconi syndrome to only low molecular weight proteinuria, hypercalciuria and little kidney disease in the first decade of life. All develop chronic kidney disease (CKD) that typically progresses slowly and reaches stages 4–5 after the second or third decade. All have neurological dysfunction, including developmental delay, marked intellectual impairment and behavioral abnormalities; ∼50% have seizure disorder. Congenital cataracts with or without glaucoma are almost always present. Less common features are hypotonia, bone abnormalities unrelated to kidney disease, abnormal teeth, cryptorchidism, skin cysts and mild bleeding disorder. Although Lowe syndrome is a monogenic disease, genotype/phenotype correlation is difficult to establish. Ubiquitous expression and complexity of Ocrl1 function likely contribute to the elusiveness of correlation. Additionally, two diseases, Lowe syndrome and Dent disease type 2, result from mutations in the OCRL gene with some overlap in affected exons. Growing research in molecular and conformational abnormalities of Ocrl1 variants is triggering development of cell phenotype models for further study. Understanding how genotype leads to clinical phenotype has potential to provide better predictors of Lowe syndrome severity and specific therapeutic strategies for different subsets of affected patients.